2005
DOI: 10.1021/jp0525437
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Bonding to π-Systems of Indole and 1-Methylindole:  Is There Any OH···Phenyl Bond?

Abstract: The weak hydrogen-bonded complexes between proton donors and the pi-cloud of indole and 1-methylindole (MI) are investigated theoretically by three different methods: DFT/B3LYP, MPW1B95, and MP2. This study addresses the question as to whether the 1:1 complex can only form between the proton and the pi-cloud of the pyrrole part of indole or if there also exists a 1:1 complex between the proton and the pi-cloud of the phenyl ring. For the water-indole system, the more elaborate MP2 and MPW1B95 methods yield onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
0
37
0
2
Order By: Relevance
“…The oxygen atom of this MI-TFE complex is further stabilised by hydrogen-bonding interaction with a second alcohol molecule, to give a ternary 1:2 complex. However, Ceulemans and coauthors [13] have discussed the validity of our theoretical calculations arguing, as other authors [14,15], that B3LYP density functional does not properly describe this kind of hydrogen bond. Ceulemans and coauthors [13] used the meta hybrid MPW1B95 density functional to demonstrate that MI-TFE p-complexation is not restricted to the pyrrole system, but it can also occur on the phenyl moiety of the indole ring with comparable interaction energies.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The oxygen atom of this MI-TFE complex is further stabilised by hydrogen-bonding interaction with a second alcohol molecule, to give a ternary 1:2 complex. However, Ceulemans and coauthors [13] have discussed the validity of our theoretical calculations arguing, as other authors [14,15], that B3LYP density functional does not properly describe this kind of hydrogen bond. Ceulemans and coauthors [13] used the meta hybrid MPW1B95 density functional to demonstrate that MI-TFE p-complexation is not restricted to the pyrrole system, but it can also occur on the phenyl moiety of the indole ring with comparable interaction energies.…”
Section: Introductionmentioning
confidence: 72%
“…However, Ceulemans and coauthors [13] have discussed the validity of our theoretical calculations arguing, as other authors [14,15], that B3LYP density functional does not properly describe this kind of hydrogen bond. Ceulemans and coauthors [13] used the meta hybrid MPW1B95 density functional to demonstrate that MI-TFE p-complexation is not restricted to the pyrrole system, but it can also occur on the phenyl moiety of the indole ring with comparable interaction energies. Consequently, these authors re-interpreted our experimental data in terms of two separate 1:1 MI-TFE complexes with the alcohol OH group attached, respectively, to the pyrrolic and phenyl moieties of the MI ring.…”
Section: Introductionmentioning
confidence: 72%
“…The groundstate hydrogen-bonded complexes of some related molecules, such as benzonitrile, [26,27] para-aminobenzonitrile, [28,29] DMABN, [30] and (methyl-)indole, [31] had previously been studied both experimentally and theoretically. Based upon these studies, we considered four complexes (visualized in Figure 9) for CMI.…”
Section: Ab Initio and Dft Calculations Of Hydrogen-bonded Complexes mentioning
confidence: 99%
“…It has been demonstrated that for weak hydrogen-bonded complexes, the MPW1B95 functional (modified Perdew and Wang exchange and Becke's 1995 correlation functional) provides results close to those of the more elaborate MP2 method, while the more recognized functionals, such as B3-LYP (Becke 3-parameter Lee-Yang-Parr exchange-correlation functional), [32,33] exhibit poor performance and may give qualitatively incorrect results. [31] To verify the performance of the MPW1B95 functional for the studied systems, the geometry of the collinear CN-H 2 O complex of CMI was optimized by MP2 with the 6-31 + + G** basis set. The deviation of DFT (with respect to MP2) for the …”
Section: Ab Initio and Dft Calculations Of Hydrogen-bonded Complexes mentioning
confidence: 99%
“…(2-propanol) complexes. The 2-propanol molecule has two rotational conformers, the structural forms of which have been theoretically studied in [12]. Figure 1e shows the calculated optimized equilibrium configuration of the carbazole complex with 2-propanol in the gauche conformation of the alcohol, and the experimentally recorded fluorescence excitation spectrum of carbazole complexes with a 2-propanol molecule.…”
Section: Carbazole-c 3 H 7 Oh (1-propanol) Complexesmentioning
confidence: 99%